The role of e-malls in B2C e-commerce: a classification framework and the comparison between Italian and US cases. (1st September 2004) - Balocco, Raffaello; Rangone, Andrea; Cardano, Paolo; Valacca, Rodolfo
In recent years, e-malls have played an important role in the B2C e-commerce landscape. Nevertheless, little attention has been paid in academic and professional literature to the analysis of this e-commerce model. The goal of the paper is to provide a detailed picture of the e-mall landscape in Italy, to propose a classification framework to define the essence of the different e-mall business models and to carry out a benchmark analysis with best practices in the USA to highlight the main differences between the Italian and the American markets.